Quantifying Musical Element Recognition in Early Childhood: A Body Movement Analysis Approach - Sano, Mina (An Overview of Literature, Language and Education Research Vol. 7, 2024)
It is widely viewed that music has the capacity to induce human body movements. Such movements range from small body parts action to full body dance. At the same time, music educators of early childhood children generally experience such movements evolve as children advance in the development stage of recognition of musical elements. Such progress is often perceived as consistent by expert educators, however, movement sophistication was hard to quantify. In this study, the author presents methods to objectively track the musical development of children by statistically processing data obtained from a 3D motion capture system. The author first, devised a four-phased Music Expression Bringing-up (MEB) program to enhance music recognition of children and devised associated the Music Test. The Music test consists of 6 areas in which each area includes 10 test items to evaluate recognition achievements based on the respective development phase. Secondly, the change in body movement in musical expression was quantitatively analyzed utilizing the MVN system as 3D motion capture by every phase of the MEB program during the practice for 3-year-old, 4-year-old and 5-year-old children. In motion capture study, 3-year-old (n=112), 4-year-old (n=94), and 5-year-old (n=111) children participated in each phase’s activity of MEB program from 2016 to 2019. Secondly, 4-year-old and 5-year-old children participated in the Music Test at the beginning of the first phase and the end of the fourth phase of MEB program practice. Thirdly, a quantitative analysis was carried out regarding both the data of body movement in musical expression and Music Test scores. As a result, applying such movement results of 4 and 5-year-old children at multiple development phases with MEB program results of relevant phases, a statistically significant relationship was attained in the analysis of variance and the relationship was depicted in Circular Affect. Results indicated as the activity phase progressed and the recognition of musical elements increased, characteristic changes in the movements of the right hand were observed, such as an increase in the moving average acceleration in the third phase of the MEB program. The integration of 3D motion capture with the MEB program provides a quantitative method for assessing musical element recognition in early childhood, offering educators a tool to track developmental progress through body movement analysis.